Translatable reporting of energy demand and rates in electrochemical carbon capture - Jonathan Boualavong; Christopher A. Gorski; Yayuan Liu (iScience)
Summary: Electrochemical carbon capture has recently emerged as a viable alternative to temperature-swing carbon capture due to its comparatively low energy demands. However, as a new research area, the experimental and measurement practices have not been standardized, making it difficult to make comparisons among studies. Guided by questions of relationships, we critically review the energy and rate evaluation metrics in the electrochemical carbon capture literature to develop a set of guidelines to make new studies more meaningful and useful for future technology transfer efforts. We demonstrate the need both for more transparent reporting due to the ways that experimental choices such as feed and outlet gas compositions influence these metrics and for careful consideration of how experimental details translate to practical applications at scale. This work is centered on capture from stationary energy generators but briefly mentions special considerations when applying the technology to direct air capture.